Level of Use and Satisfaction of E-Commerce Customers in Covid-19 Pandemic Period: An Information System Success Model (ISSM) Approach - Dirgantari, Puspo Dewi; Hidayat, Yusuf Murtadlo; Mahphoth, Mohd Halim; Nugraheni, Rury (Universitas Pendidikan Indonesia, 2020)
Pandemic outbreaks of COVID-19 have made customers take drastic steps to help world governments to prevent further spread, one of which is by social distancing. This policy made buying and selling online a convenient option to fulfill the needs for goods and/or services. The purpose of this study was to determine the level of use and satisfaction of e-commerce customers in the COVID-19 pandemic period with the information system success model (ISSM) approach that was formed through system quality, information quality, and service quality. The research method used a quantitative approach by distributing questionnaires to respondents of 206 e-commerce costumers. Data analysis used Structural Equation Modeling (SEM) where the results confirm that system quality, information quality, service quality, affected the level of use and user satisfaction of e-commerce customers. E-commerce companies are recommended to maintain, even improve system quality and information quality because information that is less interesting, less relevant, and difficult to understand results in low information quality, which in turn, can reduce the level of use and customer satisfaction.